Commentary on: Nurses’ perceptions of artificial intelligence (AI) integration into practice: An integrative review - Tania Xavier; Claúdia Oliveira (Journal of Perioperative Nursing, 2025)
We are writing this letter to congratulate you on the paper ‘Nurses’ perceptions of artificial intelligence (AI) integration into practice: An integrative review’ by Lora and Foran, recently published in your journal. In this paper the authors synthesise remarkable, valuable and challenging aspects of the new era of artificial intelligence (AI) in the clinical practice of nursing. AI has been introduced into the most diverse areas of knowledge, opening a vast range of possibilities. This integrative review makes a timely and relevant contribution to the growing body of literature on the intersection between nursing and AI. The authors show that the practice of nursing, especially in the perioperative environment, is no exception.